2011
DOI: 10.2967/jnmt.111.089961
|View full text |Cite
|
Sign up to set email alerts
|

Does 18F-FDG Uptake by Respiratory Muscles on PET/CT Correlate with Chronic Obstructive Pulmonary Disease?

Abstract: Our study revealed a strong correlation between increased (18)F-FDG uptake by respiratory muscles and the presence of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…A detailed analysis of the echographic findings may also be useful in the early diagnosis of muscle fatigue (64,65). Moreover, some imaging techniques may even allow for an approximation to the metabolic status of the respiratory muscles in both COPD patients and healthy individuals (66,67).…”
Section: Imagingmentioning
confidence: 99%
“…A detailed analysis of the echographic findings may also be useful in the early diagnosis of muscle fatigue (64,65). Moreover, some imaging techniques may even allow for an approximation to the metabolic status of the respiratory muscles in both COPD patients and healthy individuals (66,67).…”
Section: Imagingmentioning
confidence: 99%
“…Jacene et al reported in a retrospective study of 61 smokers and 35 non-smokers that increased FDG uptake in intercostal muscles is significantly more frequently seen in smokers relative to non-smokers on PET/CT [53]. Similarly, other investigators have observed increased FDG uptake on PET images in thoracic and abdominal muscles as well as in the right heart in patients with COPD [5457]. Coulson et al prospectively assessed 7 male ex-smokers with COPD and 7 male ex-smoker control patients without COPD using FDG-PET/CT, and reported that presence of COPD was associated with significantly increased aortic FDG uptake compared to controls [58].…”
Section: Discussionmentioning
confidence: 99%
“…If another muscle is considered as the reference tissue for comparison, we can easily determine whether uptake is increased in the body muscles overall or only in the respiratory muscles, as a distinctive PET study finding. REPLY: Thank you for your interest in our article (1). You have brought up very good and valid points we would like to address.…”
Section: E T T E R S T O T H E E D I T O Rmentioning
confidence: 99%